AKTIVITAS ANTIHIPERKOLESTEROLEMIA DAUN SALAM (Syzygium polyanthum): MEKANISME BIOLOGIS SENYAWA BIOAKTIF - Mi’Rajul Auliya Ulhaq; Bambang Hariyadi; Ashif Irvan Yusuf; Ahmad Sazali (UNIB Press, 2026)
Hypercholesterolemia is a major risk factor for cardiovascular disease and requires effective and sustainable management. The use of natural ingredients as alternative therapies is gaining increasing attention, including bay leaves (Syzygium polyanthum). This study is a literature review aimed at assessing the potential of bay leaves as an antihypercholesterolemic agent based on existing scientific evidence. The methods used included searching and analyzing various scientific articles covering in vivo studies, clinical trials, and in vitro and in silico approaches. The results of the review indicate that bay leaves can consistently reduce total cholesterol, LDL, and triglyceride levels, while improving the overall lipid profile; these findings are also presented in diagrammatic form to facilitate visualization of the data distribution. Identified mechanisms of action include inhibition of the HMG CoA reductase enzyme, decreased intestinal cholesterol absorption, improved lipid metabolism, and antioxidant and anti-inflammatory activities. Bioactive compounds such as flavonoids, saponins, tannins, and polyphenols work synergistically to produce multitarget effects on lipid metabolism. Several clinical trials have also shown significant effectiveness in patients with dyslipidemia, although there are variations in some parameters such as HDL. Despite its promising potential, the development of bay leaves as a clinical therapy still requires further research, particularly large-scale clinical trials, extract standardization, and long-term safety assessment. Therefore, bay leaves have the potential to be developed as an alternative or complementary herbal therapy for the treatment of hypercholesterolemia.